5‐ALA/SFC enhances HO‐1 expression through the MAPK/Nrf2 antioxidant pathway and attenuates murine tubular epithelial cell apoptosis. Issue 11 (30th September 2019) - Liu, Chi; Fujino, Masayuki; Zhu, Shuoji; Isaka, Yoshitaka; Ito, Hidenori; Takahashi, Kiwamu; Nakajima, Motowo; Tanaka, Tohru; Zhu, Ping; Li, Xiao‐Kang
Abstract : Cyclosporin A (CsA) induces tubular cell apoptosis through generating reactive oxygen species via 5/6‐chloromethyl‐2′, 7′‐dichlorodihydrofluorescein diacetateacetyl ester (CM‐H2DCFDA) and mitochondrial injury. 5‐ALA/sodium ferrous citrate (SFC) decreased ROS generation by reducing the expression of CM‐H2DCFDA and enhancing the Nrf2/HO‐1 antioxidant pathway via activation of MAPK signaling. This resulted in increased phosphoinositol p38 and Erk‐1/2, leading to the inhibition of mitochondrial apoptosis and a reduction in CsA‐induced toxicity in renal tubular cells. Abstract : Cyclosporin A (CsA) is a common immunosuppressant, but its use is limited as it can cause chronic kidney injury. Oxidative stress and apoptosis play a key role in CsA‐induced nephrotoxicity. This study investigated the protective effect of 5‐aminolevulinic acid and iron (5‐ALA/SFC) on CsA‐induced injury in murine proximal tubular epithelial cells (mProx24). 5‐ALA/SFC significantly inhibited apoptosis in CsA‐treated mProx24 cells with increases in heme oxygenase (HO)‐1, nuclear factor E2‐related factor 2 (Nrf2), and p38, and Erk‐1/2 phosphorylation. Moreover, 5‐ALA/SFC suppressed production of reactive oxygen species in CsA‐exposed cells and inhibition of HO‐1 suppressed the protective effects of 5‐ALA/SFC. In summary, 5‐ALA/SFC may have potential for development into a treatment for the anti‐nephrotoxic/apoptotic effects of CsA.